Parents' Voices Regarding Using Interventions for Toddlers With Autism Spectrum Disorder. (March 2021) - Amsbary, Jessica; Able, Harriet; Schertz, Hannah H.; Odom, Samuel L.
Parent-implemented interventions (PIIs) hold promise for young children with autism spectrum disorder (ASD) and their families. Yet, reports of parent and family perceptions regarding PIIs are limited. The present study's purpose was to gain parent perceptions regarding the helpful and challenging intervention components and contextual factors in the implementation of one PII in their daily lives. Six interviews were conducted and analyzed using an exploratory qualitative approach. Findings included considerable parent satisfaction with intervention experiences, particularly related to the use of videos taken of themselves and their children during intervention sessions. Some parents voiced discouragement after watching video examples, and parents reported challenges finding time to implement the intervention. Parents valued the supportive relationship formed with their interventionist. Additional findings and implications for research and practice are discussed.